Study on the freeze-thaw damage characteristics of skarn based on CT three-dimensional reconstruction - Shao, Zhixin; Song, Yanqi; Shen, Fuxin; Ma, Hongfa; Zheng, Junjie; Yang, Juntao (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
To study the mesoscopic damage evolution characteristics of skarn under freeze-thaw cycles, based on CT technology, the skarn samples under freeze-thaw action were scanned by CT, and the image data of skarn were segmented by Avizo software. The digital model of the three-dimensional structure of skarn was established, and the evolution law of the internal structure of skarn during the freeze-thaw cycle was quantitatively analyzed. The box dimension algorithm calculates the fractal dimension of the pore structure under freeze-thaw conditions. The relationship between fractal dimension, pore volume fraction, and freeze-thaw cycles was studied. According to the statistical results of the pore size distribu-tion of skarn, the change characteristics of pore structure in the rock under the influence of freeze-thaw were studied. Based on the theory of rock damage mechanics, the damage variable of skarn was defined using the concept of the effective bearing zone, and the freeze-thaw damage evolution of skarn was studied. The results show that the three-dimensional reconstructed model can directly show each medium’s meso-pore structure and spatial distribution. There is a positive correlation between pore volume fraction and fractal dimension under freeze-thaw conditions. The fractal dimension satisfies the exponential growth law. The skarn damage variable increases with the increase of freeze-thaw cycles, which is consistent with the development trend of pore structure. The exponential function can better reflect the damage evolution of skarn under freezing and thawing.
Mining Science, Vol. 31, 2024, s. 39-59
Keywords: górnictwo; geologia; geoinżynieria; skarn rock; freeze-thaw cycle; CT scan experiment; mesoscopic damage; damage variable